A confusion, not a system: the organizational evolution of strategic intelligence assessment in Canada, 1943 to 2003. Issue 4 (7th June 2019) - Barnes, Alan
ABSTRACT: Recently released documentation has for the first time made it possible to describe the organizational evolution of strategic intelligence assessment in Canada. During the 60-year period surveyed in this article, the analytical groups involved in strategic assessment and the interdepartmental intelligence committee structure underwent a number of changes. These were almost invariably incremental steps—shaped by bureaucratic factors and resource constraints—rather than initiatives guided by a broader vision of the role of intelligence assessment in support of Canadian foreign and defence policy. This organizational study provides the foundation for long-overdue research into the foreign intelligence function in Canada.